A Review of the Total Synthesis of (+)-Lactacystin and its Analogs - Malinak, David; Gonda, Jozef; Korabecny, Jan; Dolezal, Rafael; Honegr, Jan; Soukup, Ondrej; Buzga, Marek; Kuca, Kamil (Current Organic Chemistry, 2015)
(+)-Lactacystin (1) is a natural substance that was firstly isolated in 1991 from bacteria of the genus Streptomyces, and it was studied for its ability to inhibit cell growth. Its mechanism of action is the inhibition of the 20S proteasome, which together with two 19S regulatory sub-units makes up the 26S proteasome complex; this is a part of the ubiquitin-proteasome pathway (UPP) in eukaryotic cells. 1 accumulates particularly in damaged cells, where the misfolded proteins occur, and subsequently it is able to arrest the cell cycle in the G1 phase by inhibition of the 20S proteasome, thus inducing apoptosis of the cell. 1 and its derivatives (e.g. omuralide (2), salinosporamide A (3), cinnabaramide A (4)) were tested as potential drug candidates for the treatment of arthritis, asthma and cancer. 1 is activated in vitro at neutral pH, when there is spontaneous transformation to (+)-lactacystin-β-lactone (omuralide, 2), which is able to cross the cell membrane and irreversibly inhibit the 20S proteasome. The first total synthesis of 1 was published in 1992 by Corey et al. Soon after, different approaches to the total synthesis of 1 then followed, including formal total synthesis using various asymmetric catalyzed reactions, such as catalytic Sharpless asymmetric dihydroxylation, epoxidation, aldol condensation, Overman [3,3]-sigmatropic rearrangement and many others. This study describes the structure and function of the ubiquitin-proteasome system, and also discloses various approaches leading to the total synthesis of 1.
Keywords: proteasome inhibitor